Deixis Analysis on The Song of Meghan Trainor (English Language and Literature (JELL), 2026)
This research examines the use of deixis in the song lyrics of Meghan Trainor’s album Thank You (2016). The study aims to identify the various types of deixis and to analyze their pragmatic functions within the lyrical context. To achieve these objectives, the researcher employed a descriptive qualitative method, focusing on the linguistic nuances and contextual meanings of the deictic expressions found across the album.            The results of the study reveal a high frequency of deictic occurrences. Regarding the types of deixis, the analysis identified a total of 826 data points. Among these, person deixis emerged as the most dominant type, primarily through the use of first and second-person pronouns to establish a direct connection between the singer and the audience. Furthermore, in terms of the functions of deixis, the study identified 619 data points, with the most dominant function being identifying participants in discourse. This indicates that the lyrics are heavily centered on defining the roles of "I" (the speaker) and "You" (the addressee) to build a relatable narrative.​            The conclusion of this research highlights that Meghan Trainor utilizes deixis as a strategic pragmatic tool to construct identity and foster interpersonal negotiation within her musical discourse. By grounding the lyrics in specific personal, spatial, and temporal contexts, the songwriter effectively invites listeners into an imagined dialogic relationship. These findings underscore the importance of deixis in shaping the emotional resonance and communicative clarity of contemporary pop music.
Keywords: Pragmatics; Deixis; Song lyrics